Tau protein attenuation ability of Bacopa monnieri exract on nerve growth factor-deprived PC12 cells in normal-serum and serum-free medium - Ternchoocheep, Kanchanat; Ingkaninan, Kornkanok; Yasothornsrikul, Sukkid (Biomedical Sciences and Clinical Medicine, 2024)
Objective To study the effect of the Bacopa monnieri (BM) extract on Tau protein in nerve growth factor (NGF)-deprived PC12 cells. Methods The cells were cultured in normal-serum medium for one week before transferring to low-serum medium for the next 7 days. Then, the two cultures were raised in normal-serum or serum-free medium and treated for up to 7 days with and without 50 to 300 μg/mL of BM extract for the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide viability assay, or for 2 days with and without 50, and 100 μg/mL of BM extract for the immunoblot assay. The average percentage of cellular viability for each treatment was compared daily to that of the corresponding controls. Immunoblot assays were performed by using total Tau, dephosphorylated Tau (Tau-1), and glyceraldehydes dehydrogenase antibodies, which then quantified by Scion Image software. Tau-1 immunoreactivity was normalized by total Tau. All data were analyzed by one-way ANOVA. Results BM extract (150 and 200 μg/mL) significantly enhanced viability in NGF-deprived PC12 cells raised for four days in normal-serum medium, while BM (50 μg/mL) tended to accentuate viability in NGF-deprived PC12 cells raised for 2-4 days in serum-free RPMI (SF) medium. BM extract (100 μg/mL) could abate the amount of both total Tau and phosphorylated Tau expression in NGF-deprived PC12 cells raised in both media. Additionally, BM extract enhanced Tau-1 immunoreactivity in normal-serum NGF-deprived PC12 cells in a dose dependent manner. Conclusion This was the first study to report that BM extract could survive and attenuate the amount of both total Tau and phosphorylated Tau in NGF-deprived PC12 cells in normal-serum and serum free medium.